First record of the genus Phanoperla Banks, 1938 (Plecoptera: Perlidae) from mainland China, with description of a new species - Chen, Zhi-Teng (Zootaxa, 2020)
Phanoperla huanghuye sp. nov., a new species of Phanoperla Banks, 1938 is reported from Fujian Province of South China. This is the first record of Phanoperla from mainland China, and the third species of Phanoperla reported from China. The adult male, female, and egg of P. huanghuye sp. nov. are described and illustrated. The new species is distinctive in the male by the sensilla basiconica patches on abdominal terga 7–9, the uniquely modified hemitergal lobes and aedeagal armature. A key to the males of the three known Chinese species of Phanoperla is provided.